Autofiction and Survival - María de Souza, Eneida (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article discusses the concept of autofiction as an ambiguous pact between writing and life, between the reading and the survival of identity residues. It has to do with hybrid narratives that occupy a mobile place between novel and autobiography. These fragments of experience and self-writing have the role of scrambling the referential aspect of autobiography and the assumed autonomy of fiction. The analysis of autofictional narrative enables the characterization of reading and writing as compensation, self-help, occupation of an empty space, abolishment of the distance between art and life, and reiteration of the paradox between health and illness, death and survival.